Measuring Prospective Imagery: Psychometric Properties of the Chinese Version of the Prospective Imagery Task - Liu, Mingfan; Chen, Yiting; Yin, Xiaoying; Peng, Dandan; Wang, Xinqiang; Ye, Baojuan (Frontiers in Psychology, 2021)
Objective: Prospective negative imagery is suggested to play an important role in the development and maintenance of anxiety and depression. The Prospective Imagery Task (PIT) was developed to assess prospective imagery. Given the importance of prospective imagery for mental health in the Chinese cultural context, our objective was to examine the psychometric properties of the PIT in a Chinese sample. Methods: The instrument was validated among a sample of 1372 Chinese individuals (Mean age = 19.98, SD = 4.57; 35.2% male) who completed the PIT immediately following the Beck Depression Inventory-II (BDI-II) and State-Trait Anxiety Inventory-Trait version (STAI-T). Results: The factor structure of the PIT was in line with the original study and that the reliability was satisfactory and positively correlated with the BDI-II and STAI-T scores. The latent profile analysis revealed a three-class pattern. The measurement invariance indicated that the instrument can be used among different age groups as well as among males and females. Conclusion: The Chinese version of the PIT is a reliable and valid tool to measure prospective imagery and that the positive subscale is meaningful for clinical psychology. Limitations and future research directions are discussed.